2003
DOI: 10.1007/s00411-003-0206-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross section calculations for electron scattering from DNA and RNA bases

Abstract: Differential and integral cross sections for elastic electron collisions with uracil, cytosine, guanine, adenine and thymine have been calculated using the independent atom method with a static-polarization model potential for incident energies ranging from 50 to 4000 eV. Total cross sections for single electron-impact ionization of selected DNA and RNA bases have also been calculated with the binary-encounter-Bethe model from the ionization threshold up to 5000 eV. Cross sections within the investigated energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 19 publications
11
67
0
Order By: Relevance
“…Employed in this work, theoretical methods and computational procedures are the same as those used in our earlier works; 11,12 thus, only a brief description is provided here.…”
Section: Theory and Numerical Calculationsmentioning
confidence: 99%
“…Employed in this work, theoretical methods and computational procedures are the same as those used in our earlier works; 11,12 thus, only a brief description is provided here.…”
Section: Theory and Numerical Calculationsmentioning
confidence: 99%
“…With an identical probability for the distribution of bases in the DNA, n s for each base is 2.34 × 10 13 cm −2 , while its value for the sugar and phosphate groups is 9.36 × 10 13 cm −2 , ε i and σ i are mainly obtained from available EEL spectra; these have been measured by HREELS for the DNA bases, and tetrahydrofuran (THF) and phosphoric acid, as analogues of the sugar and phosphate groups in the DNA backbone, respectively. 21,36,37 For electron energies where such experimental data were not available, [38][39][40][41][42] The ε i and σ i were extracted from theoretical data. EEL spectra have been obtained from a single electron collision regime.…”
Section: A Nanodosimetric Modelmentioning
confidence: 99%
“…However, electron-transmission studies on the nucleobases by Gallup, Burrow, and co-workers 15,34 have revealed the energies and widths of low-energy resonances, which they have assigned as valence shape resonances associated with the vacant * orbitals. Cross section calculations have generally relied on one-electron models [35][36][37][38] and have not yielded resonance positions in good agreement with experiment. 15,34,36,38,39 In three recent papers, we have reported electron collision cross sections computed from first principles for various nucleic-acid constituents, including the RNA base uracil, 40 the purine bases and nucleosides together with the purine nucleotide deoxyadenosine 5Ј-monophosphate, 41 and the backbone sugar deoxyribose as well as its 5Ј phosphate ester.…”
Section: Introductionmentioning
confidence: 99%